Stability in Variation: Visualizing the Actantial Core of The Journey to the West,. - Wall, Barbara; Lee, Dong Myong (Korean Studies, 2023)
The urge to find the authentic original of a story seems to be a universal longing. Recently, narratologists like Barbara Herrnstein Smith, as well as experts for East Asian literatures like Michael Emmerich or Lena Henningsen, draw our attention away from the original—which is often unknowable—and instead towards the variants of a story. While this suggestion brings a breath of fresh air to the field of narrative studies, it also poses a fundamental problem. If a story does not necessarily exist as a static original, but is comprised of many variants, how should we then imagine the story itself? This paper proposes imagining the story not as a separate static unit, but rather as a story cloud that includes all variants and changes its form when new variants join, or old variants fall into oblivion. Just as it is much easier to take a picture of a static object than of a moving one, it is much easier to imagine a static text than a text in motion. The main aim of this paper is therefore to find ways to make story clouds more graspable through visualizations. Specifically, for this endeavor we will focus on one of the most popular story clouds in East Asia, The Journey to the West. Methodologically, we draw on the actant-relationship model that the computational folklorist Tim Tangherlini has developed in the article "Toward a Generative Model of Legend: Pizzas, Bridges, Vaccines, and Witches." We will apply Tangherlini's model to variants of The Journey to the West and use the data to visualize the story cloud, especially its actantial core.